Penambahan Tepung Ikan Cakalang Sebagai Sumber Protein Pada Tingkat Kesukaan Tortilla Chips - Firdaus, Nur Aini Azhar; Rostini, Iis; Arief, R. Mochamad Candra Wirawan; Pratama, Rusky Intan (Universitas Mataram, 2025)
Innovations to increase protein content in tortilla chips can be achieved by adding skipjack tuna flour. This study aims to analyze the percentage of skipjack tuna flour addition in the production of tortilla chips that are most preferred by panelists and to analyze the proximate composition of the most preferred tortilla chips. This study was conducted at the Fisheries Product Processing Laboratory, Faculty of Fisheries and Marine Sciences, University of Padjadjaran, and the Laboratory of PT Saraswanti Indo Genetech in February 2025. The research method used was experimental with 4 treatments and 25 semi-trained panelists as replicates. The treatments involved adding skipjack tuna flour to tortilla chips at levels of 0%, 7.5%, 10%, and 12.5%. The parameters observed were organoleptic characteristics (appearance, aroma, texture, taste) and chemical characteristics (protein content, ash content, fat content, moisture content, and carbohydrate content). The data obtained will be analyzed using the Friedman test and Bayes' equation. The study concluded that the addition of 12.5% skipjack tuna flour was the most preferred treatment, with an average score of 6.28 for appearance, 7.64 for aroma, 8.04 for texture, and 8.84 for taste. The alternative value for the treatment with 12.5% skipjack tuna flour addition was 8.21. The proximate analysis results of the most preferred tortilla chip treatment showed a protein content of 7.56%, ash content of 1.82%, fat content of 20.67%, moisture content of 4.35%, and carbohydrate content of 65.60%.